Recent development in mass spectrometry and its hyphenated techniques for the analysis of medicinal plants. Issue 4 (23rd April 2018) - Zhu, Ming‐Zhi; Chen, Gui‐Lin; Wu, Jian‐Lin; Li, Na; Liu, Zhong‐Hua; Guo, Ming‐Quan
Abstract: Introduction: Medicinal plants are gaining increasing attention worldwide due to their empirical therapeutic efficacy and being a huge natural compound pool for new drug discovery and development. The efficacy, safety and quality of medicinal plants are the main concerns, which are highly dependent on the comprehensive analysis of chemical components in the medicinal plants. With the advances in mass spectrometry (MS) techniques, comprehensive analysis and fast identification of complex phytochemical components have become feasible, and may meet the needs, for the analysis of medicinal plants. Objective: Our aim is to provide an overview on the latest developments in MS and its hyphenated technique and their applications for the comprehensive analysis of medicinal plants. Methodology: Application of various MS and its hyphenated techniques for the analysis of medicinal plants, including but not limited to one‐dimensional chromatography, multiple‐dimensional chromatography coupled to MS, ambient ionisation MS, and mass spectral database, have been reviewed and compared in this work. Results: Recent advancs in MS and its hyphenated techniques have made MS one of the most powerful tools for the analysis of complex extracts from medicinal plants due to its excellent separation and identification ability, high sensitivity and resolution, and wide detection dynamic range. Conclusion: To achieve high‐throughput or multi‐dimensional analysis of medicinal plants, the state‐of‐the‐art MS and its hyphenated techniques have played, and will continue to play a great role in being the major platform for their further research in order to obtain insight into both their empirical therapeutic efficacy and quality control. Abstract : The efficacy, safety and quality of medicinal plants are highly dependent on the comprehensive analysis of their chemical components; The latest developments in MS and its hyphenated technique and their applications for the comprehensive analysis of medicinal plants have been reviewed; To achieve high-throughput or multi‐dimensional analysis of medicinal plants, MS and its hyphenated techniques have played, and will continue to play a great role.